ANALISIS PENGARUH KEPEMILIKAN INSTITUTIONAL, KEPEMILIKAN MANAJERIAL, RESIKO TERHADAP KEBIJAKAN HUTANG PERUSAHAAN YANG LISTED DI BURSA EFEK INDONESIA (BEI) TAHUN 2010-2012 - Rahayuningsih, Sri (Proceeding Fakultas Ekonomi, 2014)
The purpose of this research is to examine the influence of managerial ownership, institutional ownership, risk and several control varible toward the firmâs debt equity ratio. Those control variable cover the size, dividend payout ratio, and earning volatility. This research is focuse on the manufacture firm that is listed in Indonesia Stock Exchange, along the period 2010-2012. The collecting data method that is used is pooling data, and them it is obtained 33 samples of firms, so that along that research period, those are 99 observations. Those sample are obtained based on purposive sampling and the statistical method that used is multiple regression. The result of this research shows that the factor of managerial ownership and risk are not influence, so that it is indicating that they are useless to explain and predict the factor of firmâs debt equity ratio. It is opposite to the institutional ownership that it is influence and able to predict the factor of firmâs debt equity ratio. The using of control variable in this research is to investigate the factors determining of the structure of firmâs debt equity ratio, which can be used as consideration material in determining the financing through the debt. By the result, it can be known that the firm size andÂ the earning volatility are influence. Therefore, it is indicating that the factor of size and earning volatility in this research are able to explain and predict the debt equity ratio. On the other hand, the dividend pay out ratio is not influence or cannot predict the debt equity ratio. Keywords: Institutional ownership, managerial ownership, risk, firm size, divedend pay out ratio, and earning